Investigating the Frequency of Candida glabrata in Diabetic Women of Tehran with Recurrent and Non-recurrent Vulvovaginal Candidiasis Using PCR-RFLP Assay - Mansoureh Paknejadi; Mansour Bayat; Vadood Razavilar (Pasteur Institute of Iran, 2019)
Introduction: Vulvovaginal Candidiasis (VVC) is one of the most common genital tract infections among women, especially in diabetic patients. The increasing prevalence of recurrent infections caused by drug-resistant non-albicans species necessitates further studies on diabetic patients and the identification of causative agents by reliable molecular techniques. The obtained results can assist in adopting proper treatment procedures and prevention of recurrent vulvovaginitis (RVVC). Methods: In a cross-sectional study, 150 vaginal discharge samples were collected from diabetic women suspected of candidiasis referring to health centers in Tehran province. Following the culture of samples on SDA, CHROMagar Candida and PCR-RFLP were used for presumptive and definitive identification of Candida species, respectively. Results: Out of 115 positive patients, 105 showed infection with one species, and 10 had a mixed infection with two species. The frequency of Candida glabrata isolated from non-mixed and mixed infections in RVVC group was higher than Candida albicans (27.8% vs. 9.6%), which contradicted the results of the VVC group (6.1% vs. 24.3%). In the RVVC group, therefore, the patients were more infected with non-albicans species than C. albicans (47.8% vs. 9.6%), while in the VVC group the non-albicans were of lower frequency (18.3% vs. 24.3%). Conclusion: Our findings showed a statistically significant correlation (P<0.001) between the frequency of C. glabrata and the prevalence of RVVC. On the other hand, that blood sugar, duration of diabetes, and antibiotics usage had significant correlations (P<0.001) with the recurrence of severe symptoms.